Bond modulation of MoSe2+x driving combined intercalation and conversion reactions for high-performance K cathodes. Issue 10 (20th February 2023) - Lei, Ting; Gu, Mingyuan; Fu, Hongwei; Wang, Jue; Wang, Longlu; Zhou, Jiang; Liu, Huan; Lu, Bingan
Abstract : Bond regulation not only makes the interlayer spacing larger, but also gives MoSe2+ x a double reaction mechanism combining intercalation and conversion reactions. Consequently, the capacity and energy density of MoSe2+ x can be greatly improved. Abstract : The urgent demand for large-scale global energy storage systems and portable electronic devices is driving the need for considerable energy density and stable batteries. Here, Se atoms are introduced between MoSe2 layers (denoted as MoSe2+ x ) by bond modulation to produce a high-performance cathode for potassium-ion batteries. The introduced Se atoms form covalent Se–Se bonds with the Se in MoSe2, and the advantages of bond modulation are as follows: (i) the interlayer spacing is enlarged which increases the storage space of K + ; (ii) the system possesses a dual reaction mechanism, and the introduced Se can provide an additional conversion reaction when discharged to 0.5 V, which improves the capacity further; (iii) the Se atoms confined between MoSe2 layers do not give rise to the shuttle effect. MoSe2+ x is compounded with rGO (MoSe2+ x -rGO) as a cathode for potassium-ion batteries and displays an ultrahigh capacity (235 mA h g −1 at 100 mA g −1 ), a long cycle life (300 cycles at 100 mA g −1 ) and an extraordinary rate performance (135 mA h g −1 at 1000 mA g −1 and 89 mA h g −1 at 2000 mA g −1 ). Pairing the MoSe2+ x -rGO cathode with graphite, the full cell delivers considerable energy density compared to other K cathode materials. The MoSe2+ x -rGO cathode also exhibits excellent electrochemical performance for lithium-ion batteries. This study on bond modulation driving combined intercalation and conversion reactions offers new insights into the design of high-performance K cathodes.